Two types of potential functions and their use in the modeling of information: two applications from the social sciences - Haven, Emmanuel E. (Frontiers in Psychology, 2015)
In this paper we consider how two types of potential functions, the real and quantum potential can be shown to be of use in a social science context. The real potential function is a key ingredient in the Hamiltonian framework used in both classical and quantum mechanics. The quantum potential however emerges in a different way in quantum mechanics. In this paper we consider both potentials and we attempt to give them a social science interpretation within the setting of two applications.